THE TRANSLATION OF EDUCATIONAL MATERIALS (Ustozlar uchun, 2026)
The translation of educational materials plays an important role in sharing knowledge across different languages and educational systems. Textbooks, manuals, and academic resources often require accurate translation to ensure that their meaning and educational purpose are preserved. This article examines the main aspects of translating educational materials, including common challenges and effective translation strategies.